Implementation of Multicultural Education as Efforts to Strengthen the Five Main Character Values of Student Moderation at SDN Kutuh Kintamani - Sueca, I Nyoman; Arini, Ni Wayan; Satri Adnyani, Ni Wayan; Sukerni, Ni Made; Subagia, I Nyoman (Malikussaleh University, Aceh, Indonesia, 2024)
This research aims to reveal, understand, describe, and analyze facts about implementing multicultural education as strengthening the five central values of student character in the form of moderation at SDN Kutuh Kintamani, holistically and comprehensively following the science of religious education. The type of research used was descriptive qualitative. The methods used in data collection were interviews, observations, and documentation. The technique for determining informants was carried out using purposive sampling, taking samples adapted to the research objectives, and data analysis was carried out in four ways: data collection, reduction, data presentation, and data verification. Implementing multicultural education and strengthening the five central character values is very important for students' lives in society, in addition to understanding the five central character values that the Ministry of Education and Culture has determined as a reference for realizing religious moderation to prevent discriminatory actions against different groups in society, and also embodies the spiritual teachings they adhere to. This research impacts the social life of society to understand multicultural education, which can strengthen the five central character values as a form of religious moderation established by the Ministry of Education and Culture to foster solid and reliable religious tolerance. This research focuses on a study of the implementation of multicultural education to strengthen the five central character values of students' religious moderation, which has been carried out previously.